Teste de condutividade elétrica e lixiviação de potássio para avaliação do vigor de sementes de brócolis - Silva, Isabela Carolina (2021)
The use of quality seeds in the food production chain, refers to the rapid and efficient tests that make up their vigor. The objective of the work was determined as conditions for the potassium leaching test in the evaluation of the physiological quality of seeds of two cultivars of broccoli. The results of the germination test of two cultivars evaluated classified as high and low vigor for Green Storm Bonanza with values above 90% of all discount lots, and Piracicaba Precoce shows values below 70%, with emphasis on lots 2 and 3. The electrical conductivity test shows similar results for two evaluated cultivars, with a statistical difference for the 24-hour period, for a Piracicaba cultivar where lot 3 shows a statistical difference with an average value of 90.82 µS.cm-1.g- 1, already grown in Green Storm Bonanza, presents better results in the same period for lot2 and 3 with average values of 69.60 and 59.17 µS.cm 1.g-1. Potassium leaching at different time intervals in Piracicaba did not show a statistical difference between the lots and the periods of 4, 6, 8 and 12 h of evaluation, the lots showed statistical difference in the 24 h period, where lot 2 was superior to other, with an average of 578.88 ppm K / g, followed by media of 414.50 and 306.88 ppm K / g for lots1 and 3, respectively. A Green Storm Bonanza cultivar had a low release of seed icons, making it possible to carry out a 4-hour period test, for Table 6 it was not possible to carry out the selection of lots in the periods of 4, 6, 8 and 12hs, only in 24 hours, occurring classification lot 1 high 238.34 ppm K / g, lot 2 intermediates 193.07 ppm K / g and lot 3 low 56.44 ppm K / g vigor. The electrical conductivity and potassium leaching tests show fast and consistent results for an evaluation of broccoli seed vigor, according to the tests carried out on a Green Storm Bonanza cultivar, which exerts greater vigor on its seeds when used in the early Piracicaba cultivar . Electrical conductivity and potassium leaching, in periods of less than 24 hours, are the efficient option to check the vigor of the lots